Creating Target Publics for Welfare Policies A Comparative and Multi-level Approach - Barrault-Stella, Lorenzo; Weill, Pierre-Edouard (Logic, Argumentation & Reasoning, Interdisciplinary Perspectives from the Humanities and Social Sciences, 2018)
IX, 208 p. 5 illus., 2 illus. in color.